Fouling and cleaning of polymer-entwined graphene oxide nanocomposite membrane for forward osmosis process. Issue 8 (24th May 2019) - Kim, Seungju; Ou, Ranwen; Hu, Yaoxin; Zhang, Huacheng; Simon, George P.; Hou, Hongjuan; Wang, Huanting
ABSTRACT: In this study, we have characterized membrane fouling of polymer-entwined graphene oxide membranes with a simulated feed solution containing organic foulants for wastewater treatment applications, as well as with a simulated inorganic wastewater with high iron and silicon concentrations relevant to steel industry wastewater reclamation. Membrane cleaning processes by cross-flow surface flushing with water were then applied to demonstrate water flux recovery for long-term application. Salt rejection property was retained constant during fouling process, whereas water flux was found to be reduced continuously due to fouling but was readily recoverable following surface flushing.